Designing and Implementing Practicable Data Management Plans in Large-Scale Projects - Kim, Soo-Yon; Hillemacher, Steffen; Decker, Stefan; Rumpe, Bernhard; Geisler, Sandra (Bausteine Forschungsdatenmanagement, 2023)
Creating a data management plan serves as both a suitable entry point as well as an accompanying guide to research data management for researchers. While the practice is becoming more common, it is still uncharted territory for most researchers. A comprehensive guidance as well as a facilitating environment are essential to enable researchers to integrate this practice into their everyday work. So far, little research has been directed towards the implications for the work of data stewards in this context, with hardly any recommendations on how they can provide such an enabling guidance and environment. We explored the implications in the Cluster of Excellence "Internet of Production" by conducting a series of interviews with researchers on the topic of research data management practices. Five major requirements emerged for the practicable design and implementation of a data management plan template in large-scale projects. On their basis, a customized template was created, whose project-wide implementation is currently being carried out.